Analisis Kesehatan Dan Keselamatan Kerja (K3) Dengan Metode Hazard Identification Risk Assessment and Determining Control (HIRADC) Di Peternakan Ayam Broiler Desa Wonosari - Wahyu Sidiq Saputra; Indriyani Palela (UIN Sunan Kalijaga Yogyakarta, 2023)
In an effort to fulfill animal protein and increase farmers' income, the government and breeders have made efforts to utilize most of the livestock commodity sources developed, including broilers. The application of Animal Husbandry K3 is very important to avoid occupational health and safety risks. Occupational accidents that occur in the livestock environment receive less attention because there are not many workers in the industry. By looking at the potential hazards and the large number of work accidents in the livestock industry, it is felt that there is a need for hazard analysis, risk research and risk control using the Hazard Identification Risk Assessment and Determining Control (HIRADC) method which aims to find out the hazards in Sagara Farms, find out occupational risk assessment, and what efforts should be made to reduce the risk of occupational safety and health hazards on farms.